Determinants of solid fuel use in Sub-Saharan Africa: A multilevel analysis using DHS data. - Jember Azanaw; Mastewal Endalew (PLoS ONE)
Background Dawn in human history life excessively depends on different energy sources for various purposes including cooking food and heating. Energy sources determine the economic development of the community, at the same time it is a public health problem due to environmental pollution. Worldwide Health Organization (WHO) data indicate that about 7 million deaths are attributed to indoor air pollution yearly. According to the 2019 WHO report, 90% of African people depend on dirty energy sources for domestic purposes. Understanding the prevalence and factors of solid fuel use enables policymakers to take measures to prevent its effect on public health by concerned bodies. However, research is done covering such a large area, and the sample size is limited. Therefore, the main objective of this research is to determine factors affecting solid fuel use in Sub-Saharan Africa. Methods The data source is the Demographic and Health Surveys (DHS), a regionally representative survey. Households in DHS are selected using a two-stage cluster sampling methodology. A total of 233, 391 weighted samples were included in the study. A multilevel logistic regression modeling approach was applied to estimate the influence of both individual and community-level factors on solid fuel use. Results The prevalence of solid fuel use in sub-Saharan Africa was 82.05%, with 95% CI (81.90, 82.21). Based on multilevel regression of the final model, household heads aged over 60 years (AOR = 1.12, 95% CI; 1.05-1.19), unmarried household heads (AOR = 1.14, 95% CI; 1.09-1.20), household heads no having education (AOR = 4.91, 95% CI; 4.59-5.25), poor wealth index (AOR = 12.46, 95% CI; 11.34-13.70), not watching television (AOR = 2.38, 95% CI; 2.23-2.53), households without access to electricity (AOR = 3.97, 95% CI; 3.74-4.22), Family size between four & seven (AOR = 3.94, 95% CI; 3.68-4.21), lower education levels (AOR = 2.18, 95% CI; 1.84-2.59), low media exposure (AOR = 1.39, 95% CI; 1.30-1.49), low-income levels (AOR = 63.42, 95% CI; 56.15-71.62) and being rural (AOR = 3.88, 95% CI; 3.68-4.09) were significantly associated with solid fuel use in sub-Saharan Africa. Conclusions The study showed that the prevalence of solid fuel use was high in sub-Saharan Africa. Factors such as the age and marital status of the household head, educational status of the household head, wealth index, watching television, access to electricity, family size, community-level education, community-level media exposure, residence, income level, and community-level poverty were significantly associated with solid fuel use. Solid fuel cooking has been related to respiratory and cardiovascular problems such as lung cancer, chronic obstructive pulmonary disease, and heart disease, as well as pneumonia in children, the elderly, and women who spend most of their time at home. Public health policymakers and possible stakeholders should act on poverty reduction, increase access to electricity, and educational messages through media, and increase educational infrastructures, which can minimize solid fuel use. It is also vital to raise awareness of the potential health risks related to solid fuel use in sub-Saharan Africa. Since human beings exist on land, life excessively depends on different forms of energy sources for various purposes including cooking food and heating sources. Energy sources determine the economic development of the community, at the same time it is a public health problem due to environmental pollution [1,2]. Especially using dirty energy sources like cow dung, firewood, crop residue, and charcoal are sources of indoor air pollution leading to health problems for inhabitants [3]. Worldwide Health Organization (WHO) data indicate that about 7 million deaths are attributed to indoor air pollution each year; millions more are at risk of heart attacks, lung ailments, strokes, and other respiratory and cardiovascular conditions [4]. Reports indicate that household air pollution causes an expected 1.6-3.8 million premature deaths annually [5,6].